Choledochoduodenal fistula: an unusual case of pneumobilia. (13th October 2014) - Fedidat, Raphael; Safadi, Wajdi; Waksman, Igor; Hadary, Amram
Abstract : Pneumobilia is the finding of air in the biliary tree. Most cases are iatrogenic in origin, especially after sphincterotomy and after hepaticojejunostomy or choledochojejunostomy. In patients without such history, the presence of pneumobilia needs further investigation. Most patients are likely to have an enterobiliary fistula. Although patients may be asymptomatic, possible complications include gallstone ileus, Bouveret syndrome or recurrent episodes of cholangitis. We present a case of a 38-year-old man presenting with obstructive jaundice and pneumobilia in whom choledochoduodenal fistula was diagnosed at endoscopic retrograde cholangiography. A description of different types of choledochoduodenal fistulas and management recommendations are also provided.